APPLICATION OF HYDROXYAPATITE IN PROTEIN PURIFICATION - Yusuf, Permai Sari Molyana; Dahlan, Kiagus; Witarto, Arief Budi (Makara Journal of Science, 2009)
The precursors, Na2HPO4.2H2O and CaCl2.2H2O are used for synthesizing pure hydroxyapatite which less of carbonate content. The high temperature of sintering, about 700o C of temperature, is treated to minimize the carbonate group on hydroxyapatite surface. Carbonate content of hydroxyapatite which is sintered in 700o C is less than 110o C. It indicates an increasing temperature of sintering will increase crystallinity and decrease carbonate content of hydroxapatite. This method gave better way to resulting hydroxyapatite crystal. The patterns of band of SDS PAGE in resulting of Protein Purification by DEAE matrix is also appear in using hydroxyapatite matrix. The other band also appear in purification by hydroxyapatite matrix, it showed that hydroxyapatite not only has DEAE matrix characteristic as anion exchange but also has kation exchange characteristic. These patterns proof that hydroxyapatite could be used in protein purification as matrix as cation an anion exchange. Additionally, apatite matrix is abiding and can be used repeatedly more than one hundred times without contamination.